2020
DOI: 10.1016/j.isci.2020.101878
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Tissue Engineering Tools to Interrogate Host-Microbiota Crosstalk in Cancer

Abstract: Recent studies have begun to highlight the diverse and tumor-specific microbiomes across multiple cancer types. We believe this work raises the important question of whether the classical ''Hallmarks of Cancer'' should be expanded to include tumor microbiomes. To answer this question, the causal relationships and co-evolution of these microbiotic tumor ecosystems must be better understood. Because host-microbe interactions should be studied in a physiologically relevant context, animal models have been preferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…However, novel co-culturing systems and in vitro models reproducing the gut system could be applied based on evidence of miRNA and bacteria dysregulation observed in faecal samples to improve our understanding of the molecular characteristics of this miRNA-mediated host-microbial interaction. 85 In conclusion, we hereby present the first large-scale characterisation of faecal miRNAs in relation to different diets and to the gut microbial population with the state of the art of highthroughput technologies. We show a gradual modulation of the human miRNome as a consequence of different dietary regimens with important modifications in miRNAs involved in lipid and folate metabolism.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, novel co-culturing systems and in vitro models reproducing the gut system could be applied based on evidence of miRNA and bacteria dysregulation observed in faecal samples to improve our understanding of the molecular characteristics of this miRNA-mediated host-microbial interaction. 85 In conclusion, we hereby present the first large-scale characterisation of faecal miRNAs in relation to different diets and to the gut microbial population with the state of the art of highthroughput technologies. We show a gradual modulation of the human miRNome as a consequence of different dietary regimens with important modifications in miRNAs involved in lipid and folate metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…However, novel co-culturing systems and in vitro models reproducing the gut system could be applied based on evidence of miRNA and bacteria dysregulation observed in faecal samples to improve our understanding of the molecular characteristics of this miRNA-mediated host-microbial interaction. 85 …”
Section: Discussionmentioning
confidence: 99%
“…Research on the bidirectional relation between diet and the gut microbiome has been expanded extensively using both in vivo and in vitro/ex vivo models. Udayasuryan et al ( 153 ) summarized the pros and cons of current model systems available for studying host–microbe interactions (e.g., 2D culture system, 3D organoid, gut-on-chip, and mouse). Although current research models provide a broad understanding of the effects of diet on the composition and activity of gut microbiota, there are several limitations to applying diet as a therapeutic tool with respect to reproducibility and controllability, physiologic relevance, and complexity in vivo.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Whereas BMDC activation marker expression and the innate immune cells infiltration were also performed [ 154 , 155 , 156 ]. Plus, recent research indicates that colorectal cancers include microbiota that differ from those found in a “normal” colon environment, and that these microbes might contribute to cancer growth [ 157 ].…”
Section: Cancer Diagnosticsmentioning
confidence: 99%